2012
DOI: 10.1155/2012/781765
|View full text |Cite
|
Sign up to set email alerts
|

Desmoplasia in Pancreatic Cancer. Can We Fight It?

Abstract: The hallmark of pancreatic tumours, the desmoplastic reaction, provides a unique microenvironment that affects pancreatic tumour behaviour, its ability to grow and metastasize as well as resist the effects of chemotherapy. Complex molecular interactions and pathways give rise to the desmoplastic reaction. Breakdown or penetration of the desmoplastic reaction may hold the key to overcoming the limits of delivery of efficacious chemotherapy or the development of new targeted treatments. Herein we discuss such ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 79 publications
0
53
0
Order By: Relevance
“…The function of desmoplastic stroma is likely dynamic during cancer progression and its heterogeneous cellular and non-cellular constituents change in relation to the evolving genetic landscape of cancer cells. In this regard, several studies have suggested that αSMA + myofibroblasts and type I collagen associated with tumor fibrosis are tumor promoting in solid tumors including PDAC (Angeli et al, 2009; Karnoub et al, 2007; Merika et al, 2012; Vong and Kalluri, 2011). We demonstrate that depletion of αSMA + myofibroblasts resulted in multiple adverse outcomes leading to poor survival.…”
Section: Resultsmentioning
confidence: 99%
“…The function of desmoplastic stroma is likely dynamic during cancer progression and its heterogeneous cellular and non-cellular constituents change in relation to the evolving genetic landscape of cancer cells. In this regard, several studies have suggested that αSMA + myofibroblasts and type I collagen associated with tumor fibrosis are tumor promoting in solid tumors including PDAC (Angeli et al, 2009; Karnoub et al, 2007; Merika et al, 2012; Vong and Kalluri, 2011). We demonstrate that depletion of αSMA + myofibroblasts resulted in multiple adverse outcomes leading to poor survival.…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic tumors are typically characterized by a high desmoplastic reaction (42). Desmoplasia plays an important role to initiate cross-talk between stromal-cancer cells, limit the delivery and effectiveness of chemotherapy, and induce chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, our study shows that a PLGA-CUR formulation was also highly effective in suppressing angiogenesis as indicated by a decrease in CD31(+) microvessel density (Figure 7). The PLGA-CUR induced effects were accompanied by enhanced recruitment of macrophages (Figure 7) that infiltrate the tumor, induce T cell anti-tumor immunity [43] and facilitate the depletion of the tumor stroma [54]. All together, our in vitro results demonstrate that PLGA-CUR NPs exhibit greater anti-cancer potential over free CUR by inhibiting AKT and STAT3, and inducing apoptosis, which enhance its translational value as therapeutic agents.…”
Section: Discussionmentioning
confidence: 88%